The concept of abortion in Islam and law: دراسة مقارنة - د.السر الجيلاني الأمين حماد; د.علي ميرغني أحمد (White Nile Journal for Studies and Research, 2023)
This study, entitled "The Concept of Abortion in Islam", aims to combat harmful habits and negative phenomena in Muslim society, especially illegal abortion, as well as an optional reason for this issue because the illegitimate abortion of the fetus threatens the Muslim family and criminalizes the right to life, so the problem of research on how to eliminate illegal abortion, The main findings were that the abortion of the fetus after the soul was breathed unnecessarily is forbidden, and the most important recommendations were to combat harmful customs and negative phenomena in the Muslim community. In particular the permissibility of abortion if the consent of the pregnant woman, and then the search was ended by the index of sources and references.